Exploring Police Use of Force Decision-Making Processes and Impairments Using a Naturalistic Decision-Making Approach - Hine, Kelly A. (Criminal justice and behavior, 2018)
As part of their duties, police regularly engage with citizens, which can result in the use of force. While we know how often and under what circumstances officers use force, little is known about officers’ decision-making processes that lead to force. The study took a naturalistic decision-making approach to analyze debrief sessions between 91 recruits and their trainers after partaking in a use-of-force assessment scenario. Results show recruit’s decision making was more aligned with an intuitive style rather than an analytical style. Recruits reported experiencing perceptual, cognitive, and physiological impairments that influenced the way they assessed the situation and affected their ability to successfully execute force techniques. The findings provide valuable insights into the theoretical knowledge around police decision making and how officers are making use-of-force decisions in the field. This has real-world implications for training/education and could help reduce the effects of decision-making impairments.